2016
DOI: 10.1093/toxsci/kfw073
|View full text |Cite
|
Sign up to set email alerts
|

Sirtuin 3 Protects against Urban Particulate Matter-Induced Autophagy in Human Bronchial Epithelial Cells

Abstract: Urban particulate matter (urban PM) is a heterogeneous mixture of various types of particles originating from different sources. Exposure to high concentrations of urban PM leading to adverse health effects is evaluated by using in vitro cultures of human lung epithelial cells. However, the mechanism underlying the correlation between high concentrations of urban PM exposure and adverse health effects has not been fully elucidated; urban PM-induced oxidative stress is considered as an important mechanism of ur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 81 publications
1
14
0
Order By: Relevance
“…In contrast, Sirt3 overexpression protected cells from cigarette smoke-induced damage. Thus, our results are consistent with another study, which showed that Sirt3 is protected against urban particulate matter-induced autophagy and oxidative stress in human bronchial epithelial cells [ 38 ]. Our findings improve the understanding of the role of Sirt3 in the pathogenesis of COPD and implicate the contribution of MnSOD as a mediator of tissue protection.…”
Section: Discussionsupporting
confidence: 93%
“…In contrast, Sirt3 overexpression protected cells from cigarette smoke-induced damage. Thus, our results are consistent with another study, which showed that Sirt3 is protected against urban particulate matter-induced autophagy and oxidative stress in human bronchial epithelial cells [ 38 ]. Our findings improve the understanding of the role of Sirt3 in the pathogenesis of COPD and implicate the contribution of MnSOD as a mediator of tissue protection.…”
Section: Discussionsupporting
confidence: 93%
“…Particulate matter is composed of solid and liquid particles, particularly those present in ambient air [5], and is a cause of air pollution that increases the public health risk [6]. Many studies have associated exposure to urban particulate matter (UPM) with respiratory diseases [7,8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have associated exposure to urban particulate matter (UPM) with respiratory diseases [7,8,9]. Furthermore, UPM is reported to play a role in promoting oxidative and inflammatory effects in various cells [6] and in inducing corneal cell apoptosis and inflammation [10]. However, few studies have focused on eye diseases, such as KCS, that are caused as a result of UPM exposure.…”
Section: Introductionmentioning
confidence: 99%
“…The expressions of major histocompatibility complex class II and costimulatory factors CD80 and CD86 have an important role in antigen presentation and are positively regulated by histone demethylation (Malinczak et al, 2020). Histone deacetylation by HDAC2 and HDAC6 inhibits expression of these genes (Adeegbe et al, 2017; Kong et al, 2009), Histone demethylation: JMJD3 (Gschwandtner et al, 2014), SET7/9 (He et al, 2015) Histone citrullination: PAD4 (Ham et al, 2014) DNA demethylation: TET2 (Zhang et al, 2016) Histone deacetylation: HDAC1 (Turgeon et al, 2014), HDAC2 (Turgeon et al, 2014), HDAC8 (Sanford et al, 2016), HDAC9 (Sanford et al, 2016), SIRT1 (Wang Y. et al, 2019), SIRT3 (Chen et al, 2016), SIRT6 (Zhang et al, 2018) Reduced response Figure 1. Opposing influence of epigenetic modifications on gene expression by different cell types that participate in the immune response of the skin.…”
Section: Functional Consequences Of Epigenetic Modifications Are Cellmentioning
confidence: 99%
“…Different HDACs have been reported to negatively regulate inflammatory cytokine expression by epithelia: HDAC1 in intestinal epithelial cells (Turgeon et al, 2014), HDAC2 in intestinal epithelial cells (Turgeon et al, 2014), HDAC8 in KCs (Sanford et al, 2016), HDAC9 in KCs (Sanford et al, 2016), SIRT3 in bronchial epithelial cells (Chen et al, 2016), and SIRT6 in KCs (Zhang et al, 2018) and kidney tubule epithelial cells (Gao et al, 2020). Histone demethylase KDM6A has shown activity in urothelium (Kobatake et al, 2020), histone methyltransferase G9a in KCs (Li et al, 2018), and SETDB1 in intestinal epithelial cells (Ju zni c et al, 2020).…”
Section: T Cellsmentioning
confidence: 99%